2013
DOI: 10.1093/toxsci/kft223
|View full text |Cite
|
Sign up to set email alerts
|

A Correlation Between the In Vitro Drug Toxicity of Drugs to Cell Lines That Express Human P450s and Their Propensity to Cause Liver Injury in Humans

Abstract: Drug toxicity to T-antigen-immortalized human liver epithelial (THLE) cells stably transfected with plasmid vectors that encoded human cytochrome P450s 1A2, 2C9, 2C19, 2D6, or 3A4, or an empty plasmid vector (THLE-Null), was investigated. An automated screening platform, which included 1% dimethyl sulfoxide (DMSO) vehicle, 2.7% bovine serum in the culture medium, and assessed 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium reduction, was used to evaluate the cytotoxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 36 publications
2
59
0
Order By: Relevance
“…The value of these cell lines for investigation of P450-independent and P450 metabolite-mediated cell toxicity has been demonstrated previously (Foster et al, 2013;Gustafsson et al, 2014). A marked and concentration-dependent reduction in MTS activity, which is indicative of reduced cell viability (Gustafsson et al, 2014), was observed when THLE-Null cells were exposed to sitaxentan for 24 hours ( Fig. 5A; Supplemental Table 1; Table 1).…”
Section: Resultssupporting
confidence: 71%
See 4 more Smart Citations
“…The value of these cell lines for investigation of P450-independent and P450 metabolite-mediated cell toxicity has been demonstrated previously (Foster et al, 2013;Gustafsson et al, 2014). A marked and concentration-dependent reduction in MTS activity, which is indicative of reduced cell viability (Gustafsson et al, 2014), was observed when THLE-Null cells were exposed to sitaxentan for 24 hours ( Fig. 5A; Supplemental Table 1; Table 1).…”
Section: Resultssupporting
confidence: 71%
“…The influence of P450 expression on cell toxicity caused by the ERAs was assessed using a panel of human liver-derived THLE cell lines, which expressed either no detectable P450 activities (THLE-Null cells) or the major human hepatic P450 enzymes CYP1A2, CYP2C9, CYP2C19, CYP3A4, or CYP2D6. The value of these cell lines for investigation of P450-independent and P450 metabolite-mediated cell toxicity has been demonstrated previously (Foster et al, 2013;Gustafsson et al, 2014). A marked and concentration-dependent reduction in MTS activity, which is indicative of reduced cell viability (Gustafsson et al, 2014), was observed when THLE-Null cells were exposed to sitaxentan for 24 hours ( Fig.…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations